KORUPSI BERSELUBUNG DALAM KEBIJAKAN TATA NIAGA TIMAH SEBAGAI BENTUK ANCAMAN BAGI KEAMANAN LINGKUNGAN - Djuni Thamrin (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Corruption is a major enemy of this nation that must be eradicated. The fight against various forms of corruption, from this perspective, is a dynamic within the realm of environmental security. This domain focuses on threats and risks related to the management of environmental resources, rather than threats from external aggression. It emphasizes the regulation of state resource governance to ensure that these resources are fully utilized for the welfare of the people. Public policy becomes a strategic arena that is structured to contribute to national development. However, such policies are implemented by state actors and, in practice, can be “opened up” for personal gain. Article 4, paragraph (2) of Indonesian Law No. 3 of 2020 on Mineral and Coal Mining (Minerba) states that the control of mineral and coal resources lies with the State. This means that only the central government holds the authority over their governance, which in turn centralizes the potential for corruption. This qualitative descriptive study aims to investigate how policy corruption becomes a threat to national security by further analyzing the tin trade governance within the mining concession area of PT Timah from 2015 to 2022. The academic findings conclude that in the case of the tin trade governance in PT Timah's mining concession from 2015 to 2022, state actors specifically officials from the Directorate General of Mineral and Coal at the Ministry of Energy and Mineral Resources (ESDM) unlawfully altered the 2019 Work and Budget Plan. These actions were carried out in collusion to benefit themselves and illegal tin mining operations, including foreign investors dominating this strategic sector. Novelty: The emphasis on asset recovery efforts as a form of impoverishment for corruptors, intended as a deterrent.